2021
DOI: 10.4992/jjpsy.91.18033
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-related discomforts associated with sleep characteristics

Abstract: This study investigated variations in pregnancy-related discomfort experienced, as well as their relationships with sleep during each trimester. A total of 344 pregnant women (first trimester 98, second trimester 105, third trimester 141) were surveyed using the pregnancy-related discomforts scale and the Pittsburgh Sleep Quality Index (PSQI). The nausea, shoulder discomfort, and cold hands and feet experienced during the first trimester were worse than during the third trimester. The fatigue felt during the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…A study of sleep problems in 364 pregnant women 7 and a large epidemiological study comparing sleep problems in the general population and pregnant women 8 have been reported for 20 years. A recent study has reported on the relationship between sleep and discomfort symptoms associated with the course of pregnancy 9 ; however, it did not follow the course of pregnancy after delivery. To date, no study has systematically investigated sleep during pregnancy and the postpartum period in women.…”
Section: Introductionmentioning
confidence: 97%
“…A study of sleep problems in 364 pregnant women 7 and a large epidemiological study comparing sleep problems in the general population and pregnant women 8 have been reported for 20 years. A recent study has reported on the relationship between sleep and discomfort symptoms associated with the course of pregnancy 9 ; however, it did not follow the course of pregnancy after delivery. To date, no study has systematically investigated sleep during pregnancy and the postpartum period in women.…”
Section: Introductionmentioning
confidence: 97%